C2-O-sLeX glycoproteins are E-selectin ligands that regulate invasion of human colon and hepatic carcinoma cells. - Catherine A St Hill; Dahabo Baharo-Hassan; Mariya Farooqui (PLoS ONE, 2011)
Similar to mechanisms of recruitment of activated leukocytes to inflamed tissues, selectins mediate adhesion and extravasation of circulating cancer cells. Our objective was to determine whether sialyl Lewis X modified core 2 O-glycans (C2-O-sLe(X)) present on colon and hepatic carcinoma cells promote their adhesion and invasion. We examined membrane expression of C2-O-sLe(X), selectin binding, invasion of human colon and hepatic carcinoma cell lines, and mRNA levels of alpha-2,3 fucosyltransferase (FucT-III) and core 2 beta-1,6 N-acetylglucosaminyltransferase (C2GnT1) genes, necessary for C2-O-sLe(X) synthesis, by quantitative reverse-transcriptase (RT) PCR. Synthesis of core 2 branched O-glycans decorated by sLe(X) is dependent on C2GnT1 function and thus we determined enzyme activity of C2GnT1. The cell lines that expressed C2GnT1 and FucT-III mRNA by quantitative RT-PCR were highly positive for C2-O-sLe(X) by flow cytometry, and colon carcinoma cells possessed highly active C2GnT1 enzyme. Cells bound avidly to E-selection but not to P- and L-selectin. Gene knock-down of C2GnT1 in colon and hepatic carcinoma cells using short hairpin RNAs (shRNA) resulted in a 40-90% decrease in C2-O-sLe(X) and a 30-50% decrease in E-selectin binding compared to control cells. Invasion of hepatic and colon carcinoma cells containing C2GnT1 shRNA was significantly reduced compared to control cells in Matrigel assays and C2GnT1 activity was down-regulated in the latter cells. The sLe(X) epitope was predominantly distributed on core 2 O-glycans on colon and hepatic carcinoma cells. Our findings indicate that C2GnT1 gene expression and the resulting C2-O-sLe(X) carbohydrates produced mediate the adhesive and invasive behaviors of human carcinomas which may influence their metastatic potential.